2010
DOI: 10.2174/187221310789895568
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Syndrome and Upper Airway Inflammation

Abstract: Obstructive sleep apnea syndrome (OSAS) is associated with inflammatory processes and elevated plasma cytokines. Inflammatory processes associated with OSAS may also act as potential mediators of cardiovascular morbidity in these patients. OSAS is associated with elevated levels of C reactive protein (CRP), as a marker of inflammation and cardiovascular risk. At the inflammatory point of view, the levels of TNF-alpha, IL-6, hsCRP, adhesion molecules, monocyte chemo attractant protein-1 and resist in were marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 35 publications
0
24
0
1
Order By: Relevance
“…Serum sRANKL and OPG data in the OSAS patients are documented for the first time. However, previous studies demonstrated that the concentrations of IL-6 [12,41] and TNF-α [41] were higher in plasma samples of OSAS patients. The present findings did not appear to contradict the earlier study, since higher median levels of TNF-α and IL-6 were observed in our investigation but levels in OSAS groups were not statistically significantly different from the control group serum levels.…”
Section: Discussionmentioning
confidence: 82%
“…Serum sRANKL and OPG data in the OSAS patients are documented for the first time. However, previous studies demonstrated that the concentrations of IL-6 [12,41] and TNF-α [41] were higher in plasma samples of OSAS patients. The present findings did not appear to contradict the earlier study, since higher median levels of TNF-α and IL-6 were observed in our investigation but levels in OSAS groups were not statistically significantly different from the control group serum levels.…”
Section: Discussionmentioning
confidence: 82%
“…Sleep apnea and the attendant chronic intermittent hypoxia induce CNS inflammation and impair cognitive function (Gozal, 2009, McNicholas, 2009, Ryan et al, 2009, Inancli and Enoz, 2010, Kimoff et al, 2010). If chronic intermittent hypoxia-induced inflammation alters respiratory chemoreflexes and plasticity, then disease/ventilatory control interactions may contribute to the underlying pathophysiology.…”
Section: Significance Implications and Future Directionsmentioning
confidence: 99%
“…[2] Because an altered upper airway structure and function is 1 etiology of OSA, [3,4] local pathophysiological processes such as upper airway inflammation could amplify these abnormalities and may further compromise upper airway patency during sleep. A large body of experimental evidence indicates that patients with OSA present with airway inflammation [5,6] mainly because of the mechanical trauma of recurrent snoring and oxidative stress. Furthermore, it has been reported that the repetitive hypoxia/reoxygenation phenomenon increases the levels of reactive oxygen species, which aggravate vascular endothelium injury in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%